2013
DOI: 10.1039/c2sc20846f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical biology toolkit for exploring protein kinase catalyzed phosphorylation reactions

Abstract: EDGE ARTICLEAndrew J. deMello, Joshua B. Edel et al. Rapid cell extraction in aqueous twophase microdroplet systems PERSPECTIVE Barry M. Trost et al. Catalytic asymmetric allylic alkylation employing heteroatom nucleophiles: a powerful method for C-X bond formation Abstract Current interests in biochemical transformations based on protein kinase-catalyzed phosphorylations drive the identification and characterization of biological targets and potential inhibitors of protein kinase activity. A simple transfer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 114 publications
0
9
0
1
Order By: Relevance
“…These works demonstrated that Fc‐ATP and its derivative compounds are powerful tools for protein‐kinase‐activity and inhibitor‐screening studies. Even though γ‐modified ATP was demonstrated to be acceptable as a substrate in HK‐mediated processes, Fc‐labelled ATP was still unknown . Thus, we decided to examine the usefulness of this tool in this biological process (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…These works demonstrated that Fc‐ATP and its derivative compounds are powerful tools for protein‐kinase‐activity and inhibitor‐screening studies. Even though γ‐modified ATP was demonstrated to be acceptable as a substrate in HK‐mediated processes, Fc‐labelled ATP was still unknown . Thus, we decided to examine the usefulness of this tool in this biological process (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The methods used in this burgeoning field have been recently and comprehensively reviewed from kinase identification [3], analytical chemistry [4], and chemical biology toolkit [5] perspectives and the main approaches are briefly overviewed below.…”
Section: Introductionmentioning
confidence: 99%
“…Although a variety of fluorescent sensors of protein kinases have been described, [7]–[8] strategies have not yet been developed that can tune sensors to specific wavelengths within the optical window of tissue. One appealing approach is to take advantage of the commercial availability of far-red and near-IR fluorophores.…”
mentioning
confidence: 99%